Coordinate activation of a target gene by KDM1C histone demethylase and OTLD1 histone deubiquitinase in Arabidopsis - Ido Keren; Moshe Lapidot; Vitaly Citovsky (Epigenetics, 2019)
Potential functional coordination between histone deubiquitinases and histone lysine demethylases represents one of the least studied aspects of epigenetic control of transcriptional outcomes. Here, this question was addressed using Arabidopsis histone modification erasers deubiquitinase OTLD1 and demethylase KDM1C known to interact with each other in plant cells. Characterization of gain- and loss-of-function mutants of OTLD1 and KDM1C showed that both enzymes associate with the promoter chromatin of their target gene AN3 and function as coactivators of its expression. This transcriptional outcome was underlain by demethylation of the H3K9 repression mark, presumably by the KDM1C histone demethylase activity. Association of KDM1C and OTLD1 with the target chromatin was interdependent such that OTLD1 was not detected at the AN3 in the absence of KDM1C and KDM1C displayed a different and non-functional pattern of association in the absence of OTLD1. Thus, OTLD1 and KDM1C may crosstalk with each other to assemble a functional coactivator complex at the AN3 promoter chromatin and set the KDM1C specificity for the methylated H3K9 to determine the correct transcriptional outcome.